Men judo motion analysis by weight classes - Matches held in 2012 london - Barreira, J.; Carvalho, L. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
The motions of men Judo players employing a Judo "Throwing technique" known as "Ippon" at the 2012 "London Olympics" were analyzed. Men Judo participants were analyzed according to their weight classes using motion picture data given by The Japan Judo Federation. The purpose of this study is to examine the difference of "Kake" time by weight classes. The motion picture data was disassembled into frame data called AVI, which is a file format developed by Microsoft Corp.. The motions performed by participants were analyzed using a software system implemented by us based on "OpenCV", which is an open source library developed by Intel Corp.. The beginning and ending of "Kake" time were defined. Then, the "Kake" time, which is the period of time between the beginning and ending of "Kake" according to judgements known as "Ippon," were examined. The mean value and standard deviation of the "Kake" time were statistically calculated for all weight classes by using "Excel," a spreadsheet developed by Microsoft Corp.. Then, they were compared. We found no significant difference of "Kake" time because of weight classes.